Menelaah Keabsahan Kontrak Binary Option pada Unsur Pidana Perjudian - Setiyawan, Deni; Rahmad, Noor (Jurnal Penegakan Hukum dan Keadilan, 2024)
The rapid development and advancement of technology had made everything easy, including accessing the internet. The economy is one of the many fields that have experienced rapid development as a result of technological developments, and investment is no exception. One of the investments that is currently being discussed is the binomo platform. But in reality, binomo is not an investment but a platform that provides binary option services for potential investors. The element of agreement is the most important element in determining whether binary options are included in gambling applications or not. This research aims to examine the validity of the agreement on binomo in determining whether the binary option is included in the gambling application or not. This research uses a normative juridical method with a conceptual approach. The results of this study explain that the validity of the futures contract on the binomo platform in terms of the Civil Code contradicts several articles in the Civil Code, when referring to the valid terms of the agreement in article 1320 of the Civil Code, binomo does not meet when viewed from the 3rd valid requirement, namely a certain thing and the 4th valid requirement, namely a lawful legal cause. the Binary Option Trading mechanism has fulfilled the elements of gambling in accordance with Article 303 Paragraph 3 of the Criminal Code, so that the Binary Option Trading affiliator can also be subject to Article 27 Paragraph 2 of the ITE Law Jo. Article 45 Paragraph 1 of the ITE Law.